Systemic analysis the expression, prognostic, and immune infiltrates significance of MS4A family in lung cancer. Issue 1 (31st December 2022) - Cen, Caize; Tang, Jiameng; Su, Qisheng; Zhang, Zunni; Yang, Zheng; Mo, Wuning
Abstract : With its high incidence and mortality rate, lung cancer is one of the malignancies that poses the greatest threat to the health and life of the population. Mounting research found that the Membrane-spanning 4A (MS4A) family took part in tumor development. Nevertheless, the expression and prognostic value of the MS4A family genes in lung cancer remained unclear. Compared with normal tissues, the transcript levels of MS4A2, MS4A4A, MS4A4E, MS4A6A, MS4A6E, MS4A7, MS4A8, MS4A14, and MS4A15 were significantly decreased in lung cancer tissues, and there was a significant correlation between MS4A2, MS4A8, MS4A15, and the pathological stage of lung cancer patients. Survival analysis has shown that lung cancer patients with lower mRNA expression levels of MS4A2, MS4A4E, and MS4A15 had poorer prognosis. The function of MS4A family genes was primarily involved in immune-related pathways. Based on the results, it was indicated that the expression of the MS4A family was significantly correlated with the infiltration of immune cells (B cells, CD8+ T cells, CD4+ T cells, macrophages, neutrophils, and dendritic cells). In conclusions, our research indicated that MS4A family might become a new immunotherapy target and prognostic biomarker for lung cancer.